2000
DOI: 10.1073/pnas.080421597
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous lineages of monocot flowering plants

Abstract: The phylogeny of flowering plants is now rapidly being disclosed by analysis of DNA sequence data, and currently, many Cretaceous fossils of flowering plants are being described. Combining molecular phylogenies with reference fossils of known minimum age makes it possible to date the nodes of the phylogenetic tree. The dating may be done by counting inferred changes in sequenced genes along the branches of the phylogeny and calculating change rates by using the reference fossils. Plastid DNA rbcL sequences and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
149
3
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(165 citation statements)
references
References 27 publications
9
149
3
4
Order By: Relevance
“…Thus, we began by reviewing the fossil record of Liliales, with particular emphasis on Liliaceae and its sister family Smilacaceae (comprised of Smilax L. including Heterosmilax Kunth). Bremer (2000) reviewed the Cretaceous lineages of monocots and observed that only a few systematically informative monocot fossils pre-date the K-T boundary and none of these are attributable to Liliales. Lililes-like pollen is first reported from the Aptian of the Cretaceous (125-112 Mya) and is characterized by having a broad colpus, an elongate shape, and distinctive exine sculpturing, which is finer towards the ends and coarser along the broadest section (Doyle, 1973;Muller, 1981;Friis et al, 2011).…”
Section: Dating the Times Of Divergencementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we began by reviewing the fossil record of Liliales, with particular emphasis on Liliaceae and its sister family Smilacaceae (comprised of Smilax L. including Heterosmilax Kunth). Bremer (2000) reviewed the Cretaceous lineages of monocots and observed that only a few systematically informative monocot fossils pre-date the K-T boundary and none of these are attributable to Liliales. Lililes-like pollen is first reported from the Aptian of the Cretaceous (125-112 Mya) and is characterized by having a broad colpus, an elongate shape, and distinctive exine sculpturing, which is finer towards the ends and coarser along the broadest section (Doyle, 1973;Muller, 1981;Friis et al, 2011).…”
Section: Dating the Times Of Divergencementioning
confidence: 99%
“…Lililes-like pollen is first reported from the Aptian of the Cretaceous (125-112 Mya) and is characterized by having a broad colpus, an elongate shape, and distinctive exine sculpturing, which is finer towards the ends and coarser along the broadest section (Doyle, 1973;Muller, 1981;Friis et al, 2011). However, since similar pollen occurs elsewhere among the monocotyledons, this type is not definitively attributable to Liliales (Doyle, 1973;Daghlian, 1981;Bremer, 2000;Friis et al, 2011). Thus, microfossils are not useful for divergence time dating within Liliales or subordinate genera.…”
Section: Dating the Times Of Divergencementioning
confidence: 99%
“…The split between Acorus and the remaining monocots was estimated to be more than 134 mya by Bremer (2000) and between 127-141 mya by Wikström et al (2001) based on chloroplast data and multiple fossil calibrations. This result is in agreement with Good-Avila et al (2006) based on rbcL and trnL-F data and have been adopted by Janssen and Bremer (2004).…”
Section: Dating the Times Of Divergencementioning
confidence: 99%
“…To calibrate the trees, the minimum age of Gentianales was estimated to be 60 million years (MY) based on pollen fossil data (Muller, 1984). As an independent test for the divergence times based on rate smoothening, the branch-specific rate dating method based on the mean branch length (MBL) as implemented in Bremer (2000) and Patterson and Givnish (2002) was used to obtain estimations of the divergence times using the same calibration point. The six equally most parsimonious trees generated by heuristic searches using Ôminimum as zeroÕ branch collapse option, were examined.…”
Section: Divergence Time Calculationsmentioning
confidence: 99%
“…Divergence times are shown in million years before present (MY). NPRS, non-parametric rate smoothing (Richardson et al, 2001a;Sanderson, 1997); MBL, mean branch length (Bremer, 2000;Patterson and Givnish, 2002); MC, molecular clock; CP, calibration point based on fossil pollen date (Muller, 1984).…”
Section: Monophyly Of Exaceae and Its Relationships With Other Tribesmentioning
confidence: 99%